Photoquenching indications of a thermally triggered transition between two different EL2 metastable states in GaAs - Fávero, Priscila Pereira (2006)
In this work we report the observation of two different EL2 metastable states in GaAs and the effect of the optical/thermal history of the sample on the behavior of the photoquenching kinetics. In one thermal/optical preparation, the photoquenching curve presented two time constants that have already been interpreted as an indication of two different metastable states. With another preparation, the initial rise in transmittance displayed only one time constant, and we observed that a temperature increase to 83K triggered a second photoquenching process. We associated this new photoquenching with a transition from the first to the second metastable state. The experimental data is explained in terms of a new proposal for the microscopic structure of the EL2 complex.